Global Tourism Trends and their Impact on International Tourism in Vietnam - Khuc, Thuy Quynh (2023)
This diploma thesis delves into the realm of global tourism trends and their impact on rapidly developing nations, with a specific focus on Vietnam, a burgeoning tourism hotspot in South-East Asia. Employing an applied approach, the study aims to discern the most influential global tourism trends and their significance for Vietnam's international tourism, as perceived by key stakeholders in the tourism industry. Additionally, it scruti- nizes how these trends align with Vietnam's official Tourism Development Strategy while identifying potential gaps in strategic planning. To address these gaps, the thesis furnishes a comprehensive set of recommendations, offering invaluable guidance to optimize the utilization of global tourism trends for the Vietnamese government. Employing a qualita- tive research methodology, the thesis synthesizes insights from a diverse range of primary and secondary sources, including UNWTO documents, national strategic materials, and insightful semi-structured interviews with representatives from the travel and tourism sec- tors.